2006
DOI: 10.1002/cbf.1344
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypobaric hypoxia‐induced oxidative stress in rat erythrocytes: protective effects of vitamin E, vitamin C, and carnitine

Abstract: This study was aimed at determining the effect of vitamin E, vitamin C, and carnitine on intermittent hypobaric-hypoxia-induced oxidative stress (OS) in erythrocytes. For this purpose, male Wistar rats of 4 months of age were orally supplemented with one of the antioxidants prior to exposure to altitudes of 5700 m or 6300 m. Hemoglobin (Hb) and OS indices such as osmotic fragility and hemolysis were measured together with lipid peroxidation (LPO) and protein oxidation. The increase in Hb was accompanied by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…Indeed, VC reacts with oxygen free radicals and has the potential to protect both cytosolic and membrane components of cells from oxidative damage under hypobaric hypoxic stress (110). Moreover, Kim et al demonstrated that VC was able to reduce apoptosis in bovine ovarian cortex (111).…”
Section: H) Hypoxiamentioning
confidence: 99%
“…Indeed, VC reacts with oxygen free radicals and has the potential to protect both cytosolic and membrane components of cells from oxidative damage under hypobaric hypoxic stress (110). Moreover, Kim et al demonstrated that VC was able to reduce apoptosis in bovine ovarian cortex (111).…”
Section: H) Hypoxiamentioning
confidence: 99%
“…Hypoxia increases oxidative stress both in humans and in rodents (Radak et al, 1997;Asha Devi et al, 2005;Devi et al, 2007;Pialoux et al, 2009). It has been shown that supplements with antioxidant mixtures can compensate for the decline in membrane stability following intermittent hypobaric hypoxia as a consequence of decreased lipid peroxidation (LPO) and protein oxidation (Devi et al, 2007;Vani et al, 2010). The vast majority of endurance athletes, including elite athletes, take vitamin supplements such as vitamin C, often in large amounts (Sobal and Marquart, 1994), as an antioxidant and antianemic tool.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of oxidative stress by hypoxic exposure in RBC has been described by Devi et al (2007) and Vani et al (2010). Devi et al (2007) exposed Wistar rats to the altitude of 5700-6300 m to examine the effects of hypoxia on oxidative stress in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of oxidative stress by hypoxic exposure in RBC has been described by Devi et al (2007) and Vani et al (2010). Devi et al (2007) exposed Wistar rats to the altitude of 5700-6300 m to examine the effects of hypoxia on oxidative stress in erythrocytes. These investigators reported that osmotic fragility, hemolysis, and lipid peroxidation increased in erythrocytes following intermittent hypobaric-hypoxic exposure (Devi et al, 2007), suggesting that low ambient oxygen induces oxidative stress in erythrocytes and might subsequently impair hemoglobin oxygen-carrying capacity.…”
Section: Discussionmentioning
confidence: 99%